Combit response to COVID-19 pandemic in Odisha: future public health challenges and measures - Swain, Dharitri; V. R., Vijay; Das, Hrushikesh; Issac, Alwin; Stephen, Shine; Jacob, Jaison (International Journal Of Community Medicine And Public Health, 2021)
COVID-19 is considered as a public health emergency of International concern (PHEIC) and thus a pandemic with an explosive increase rate of infection worldwide. The mobilization of resources to prevent and treat COVID-19 infections is unparalleled in the history of public health. Different measured has been adopted by the different state to fight against COVID-19. The preparedness level to control this pandemic has been rapid and unprecedented and made possible by the coordination between center and state govt. To minimize the infectivity and controlling the COVIID-19 disaster, Odisha was the first state to announce lockdown 2.0, following strict quarantine guidelines, community monitoring for home quarantine people, and extending care by establishing COVID hospital. This paper is based on a review of the preparedness strategy adopted in Odisha state govt. for controlling COVID-19. The major objective was to review the recent preparedness level in the state of Odisha for maintaining a very low mortality rate and could be used as a model to deal with future challenges for effectively handling COVID-19. We searched literature related to COVID -19 published between December 20, 2019, and August 31, 2020, in the website archive of the Ministry of health and family welfare Government of India and Odisha, journal repositories such as Google Scholar, Pub Med, Science Direct, etc. We identified 35 studies that met the search criteria for inclusion in the review. The review would be useful for adopting a community preparedness and complication readiness model for effective management of COVID-19 cases.